Iranian nongovernmental organizations' initiatives in COVID-19 pandemic - Meroe Vameghi; Monir Baradaran Eftekhari; Katayoun Falahat; Ameneh Setareh Forouzan (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: With the outbreak of the COVID-19 virus crisis worldwide, including Iran, the need for corona prevention and treatment has become a national priority. With many businesses closed in the wake of COVID-19 and job losses and declining incomes, vulnerable individuals' and families' access to the minimum wage and healthcare facilities is falling, and their health is exposed to a great risk. In Iran, a significant number of vulnerable groups are supported by nongovernmental organizations (NGOs). This study is designed to understand the performance of NGOs after the onset of the COVID-19 crisis. MATERIALS AND METHODS: This study was carried out based on qualitative research between June and September 2020 in Tehran. This study was conducted using individual interviews with 33 managers and experts of 24 active NGOs providing services to vulnerable groups and a member of an NGO network. Data were analyzed using content analysis. RESULTS: Two main themes of service initiatives were extracted: (a) service initiatives to protect the target population against COVID-19 infection and its aftermath and (b) management initiatives to retain staff, finance, and adapt the organization to crisis situations. Service initiatives included five categories of health service initiatives, livelihood, employment, education, and leisure initiatives, while organizational management initiatives include human resource management, financial management, and communication with organizations. CONCLUSION: The COVID-19 breadth and its special features have set it apart from other crises and have led NGOs to work hard on several fronts to care for the most vulnerable people against the epidemic and its consequences and maintain the performance of their organizations. The unique role of cyberspace has made it one of the definitive pillars of the activities of NGOs, not only during the epidemic but also after its end.